Prototipe Sistem Keamanan dan Kenyamanan Gedung Olahraga Berbasiskan Mikrokontroller - Liawatimena, Suryadiputra (ComTech: Computer, Mathematics and Engineering Applications, 2010)
This study is intended as a source of learning and research will design and comfort safety System gymnasium-based microcontrollers. Existing gym until now still has a weakness for several factors such as weather changes rapidly, visitors are crowded, and the level of public awareness of the order is still lacking, so will implications for the safety and comfort for users of building itself. The method is a method of research literature and methods of laboratory studies. Literature study was done by studying and looking for articles on matters relating to the development of world sports stadiums that are considered to have the required criteria. For laboratory study done by making the design of hardware and software is also used in this study. This system used sensors to detect the rainy weather conditions, detect the light intensity to keep the lighting inside the building, limiting the number of visitors in accordance with the capacity building capacity, temperature rise resulting from a user density of buildings and also a fire hazard that could have been either intentional or unintentional. Entirety of the sensor arrangement is controlled by a microcontroller. It is expected that by using this system, users are building (football stadium) will feel more secure and convenient to activities inside the building.